2019
DOI: 10.1039/c9cp03071a
|View full text |Cite
|
Sign up to set email alerts
|

Auramine O interaction with DNA: a combined spectroscopic and TD-DFT analysis

Abstract: AuO fluorescent molecular rotor intercalation into DNA: calculations and experiments uncover binding details as absorbance/fluorescence features, energies involved and geometries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In terms of binding mode, some of the previous reports revealed that AuO binds strongly to the minor groove formed by the AT region of the DNA . On the other hand, few reports have observed that AuO can bind exclusively by the intercalation binding mode or by a mixture of intercalation and groove binding modes. , Generally, the surface of minor grooves with AT-rich sequences has the highest negative electrostatic potentials . Naturally, the cationic AuO prefers to bind to the AT-rich minor grooves of DNA than the minor groove formed by the GC-bps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of binding mode, some of the previous reports revealed that AuO binds strongly to the minor groove formed by the AT region of the DNA . On the other hand, few reports have observed that AuO can bind exclusively by the intercalation binding mode or by a mixture of intercalation and groove binding modes. , Generally, the surface of minor grooves with AT-rich sequences has the highest negative electrostatic potentials . Naturally, the cationic AuO prefers to bind to the AT-rich minor grooves of DNA than the minor groove formed by the GC-bps.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from protein, it can also bind to DNA . Although there are few reports on the interaction between AuO and polymeric double-stranded (ds) DNA (calf thymus DNA), a comprehensive and conclusive study based on the effect of the DNA sequences on the photophysics of AuO is hitherto unexplored. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the liberated portion I (GTrich sequence) coiled together into G4cpx in the presence of AuO dye (G4cpx-AuO) due to the π stacking interaction between the guanine bases and AuO and the protonated imine group between two electron-rich nitrogen atoms in its structure leads AuO to be a molecular fluorescent rotor. The interaction of AuO in G4cpx DNA prevents the rotation of the C-C bond in AuO structure and prevents the intramolecular charge transfer from an emissive to a nonradiative state [25], resulting in the remarkable AuO emission. The increase in fluorescence intensity was computed as the signal gain for the L-His quantification through F/F 0 , where F 0 and F are the fluorescence intensities before and after the L-His DNAzyme reaction, respectively.…”
Section: The Proposed Sensing Mechanismmentioning
confidence: 99%
“…Furthermore, the AuO with DNAzyme exhibits a strong peak at 432 nm; however, in the presence of L-His, the spectra gradually decrease the intensity and the maximum shifts toward the red, moving from 432 to 444 nm for bound AuO (inset right). Hypochromic and bathochromic effects are often anticipated as an indication for AuO dye intercalation [25].We employed circular dichroism spectroscopy (CDS) to further prove the conformational change in the DNAzyme caused by L-His. Figure 4C shows a strong positive peak at 274 nm, and a negative peak at 243 nm, and these peaks correspond to the characteristics peak of the duplex DNAzyme (curve a).…”
Section: Confirmation Of the Dnazyme Cleavage By L-hismentioning
confidence: 99%